Effect of welding parameters on microstructure and mechanical properties of friction stir welded Al 6061 aluminum alloy joints. (2020) - Choudhary, Saket; Choudhary, Sahaj; Vaish, Siddharth; Upadhyay, Avani Kumar; Singla, Amneesh; Singh, Yashvir
Abstract: In present work, FSW of Al 6061 was performed at different parameters. Effect of a number of pass and tool rotational speed on hardness and metallurgical properties were analyzed. Vickers hardness test, optical microscopy, and XRD test were performed for concluding the optimum set of parameters. The increment in the micro hardness was observed with increase in the number of passes. Joint produced at 950 rpm and 3 weld pass give maximum hardness i.e. around 85 HV. Hard precipitates of Al2 O3 is reported. Microstructural investigation reveals that grain size decreases with the number of weld passes and increases with rotational speed.